Analisa Pengaruh Variasi Pelumas terhadap Keausan Baja St 60 dengan Tribometer Pin-On-Disc - Ihsan Nur Roziqin (Universitas Muhammadiyah Yogyakarta, 2023)
Pin-On-Disc is a tool used to test a material's friction and wear levels. This tool is also one of the tribometer components. Pin-on-Disc uses a ball-shaped pin and a disk of ST 60 wrought iron as a disc in this test. This test aims to see or determine the volume of wear produced by pins with SAE40 and SAE140 lubricants and the importance of pin wear without lubrication. Lubrication influences the material or test specimen in this tribometer test. In this test, they are using a simple Pin-on-Disc Tribometer. The results obtained from this test are that the test without using lubricant shows at coordinates 0.0704 N, while the test with SAE40 lubricant shows at coordinates 0.07027 N, and testing with SAE140 lubricant is at coordinates 0.0703N.